2020
DOI: 10.1021/acs.jmedchem.9b01953
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 4-Phenylpiperidine-2-Carboxamide Analogues as Serotonin 5-HT2C Receptor-Positive Allosteric Modulators with Enhanced Drug-like Properties

Abstract: Targeting the serotonin (5-HT) 5-HT 2C receptor (5-HT 2C R) allosteric site to potentiate endogenous 5-HT tone may provide novel therapeutics to alleviate the impact of costly, chronic diseases such as obesity and substance use disorders. Expanding upon our recently described 5-HT 2C R-positive allosteric modulators (PAMs) based on the 4-alkylpiperidine-2carboxamide scaffold, we optimized the undecyl moiety at the 4position with variations of cyclohexyl-or phenyl-containing fragments to reduce rotatable bonds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…This distinct new binding site may play an important role in biological modulation of BRD4-associated protein–protein interactions. Given the complicated action modes of allosteric modulators, ,, further studies are needed to elucidate the possible allosteric binding mechanism of 52 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This distinct new binding site may play an important role in biological modulation of BRD4-associated protein–protein interactions. Given the complicated action modes of allosteric modulators, ,, further studies are needed to elucidate the possible allosteric binding mechanism of 52 .…”
Section: Resultsmentioning
confidence: 94%
“…Additional binding affinities for other bromodomain-containing proteins were investigated for compounds 52 and 53 to evaluate their selectivity over other BET members (e.g., BRD3 and BRDT) and non-BET protein (e.g., CBP). For compound 52, we also conducted non-BET protein panel screening through Discov-erX (Supporting Information, Table S2) and an additional comprehensive screening against more than 40 drug targets from the NIMH psychoactive drug screening program as described in our previous publications 53,54 to evaluate the potential off-target effects (Supporting Information, Table S3). Excitingly, this extensive screening endeavor indicated that 52 maintains an overall excellent drug target specificity profile with no or weak binding affinities toward these screened drug targets.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In parallel with drug discovery, the development of subtype-selective PET tracers could improve the understanding of related 5-HTRs. Most recently, several molecules with the 4-alkylpiperidine-2-carboxamide scaffold were developed as effective 5-HT 2C PAMs with subtype selectivity. , Among them, CTW0415 ( 190 , Figure ) was discovered to have significant PAM activity at 5-HT 2C but not 5-HT 2A receptor and thus suitable for in vivo pharmacological studies of allosteric modulation. In addition, many allosteric modulators could affect 5-HT 3 receptors’ function, for example, n -alcohols, anesthetics, cannabinoids, opioids, and steroids, and these compounds act at 5-HT 3 receptors as either PAMs or NAMs.…”
Section: Perspectives For 5-htr Pet Ligand Developmentmentioning
confidence: 99%
“…Furthermore, it exhibited a favorable pharmacokinetic profile, potentiated 5-HT 2C -mediated suppression of spontaneous locomotor activity in rodent, and attenuated impulsive action and sensitivity to cocaine-associated cues in a preclinical self-administration model [ 98 ]. Finally, in a last optimization hit, the same group synthetized and tested a new positive allosteric modulator of 5-HT 2C receptor, CTW0415 [ 97 ]. On the basis of the 4-alkylpiperidine-2-carboxamide scaffold, they optimized the undecyl moiety at the 4-position with phenyl-containing fragments to reduce rotatable bonds and lipophilicity.…”
Section: Exogenous Allosteric Modulator Of Serotonin Receptorsmentioning
confidence: 99%